2008
DOI: 10.3390/ijms9122658
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Models Reveal the Two-component Mechanics of Striated Muscle

Abstract: This paper provides a comprehensive explanation of striated muscle mechanics and contraction on the basis of filament rotations. Helical proteins, particularly the coiled-coils of tropomyosin, myosin and α-actinin, shorten their H-bonds cooperatively and produce torque and filament rotations when the Coulombic net-charge repulsion of their highly charged side-chains is diminished by interaction with ions. The classical "two-component model" of active muscle differentiated a "contractile component" which stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 222 publications
0
18
0
Order By: Relevance
“…For example, an in vitro motility assay demonstrated that actin filaments gliding over a myosin-coated coverslip surface can rotate around their long axis 61,62 and form a superhelix 63 . Also, the actin filament can undergo a rolling sliding motion in sarcomeres 64,65 . The torque may cause the generation of torsion in the myofilaments as sarcomeres contract.…”
Section: Scientific Reportsmentioning
confidence: 99%
“…For example, an in vitro motility assay demonstrated that actin filaments gliding over a myosin-coated coverslip surface can rotate around their long axis 61,62 and form a superhelix 63 . Also, the actin filament can undergo a rolling sliding motion in sarcomeres 64,65 . The torque may cause the generation of torsion in the myofilaments as sarcomeres contract.…”
Section: Scientific Reportsmentioning
confidence: 99%
“…A series of steps should produce more friction since the redeveloped force after each quick release depends on additional internal rotation during rewinding the Z-filaments [2]. …”
Section: The Underlying Mechanicsmentioning
confidence: 99%
“…Heat also increases glycogen resynthesis and muscle recovery [10]. Heat is also cited as increasing flexibility and thus reducing the chance of injury, and reducing energy cost of muscle contraction by reducing internal friction [11,12]. Internal energy costs are reduced by warming muscle, but many of these studies have been done in animals and very few in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The response of stretch receptors in the cat are also increased by heat [15]. The mechanism of the changes in the series’ elastic component is partly due to unwinding of the actin filaments in muscle due to stretch and partly due to collagen relaxation [11,12]. There is also rotation of the actin filaments with heat [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation